Does Tabletop Exercise Enhance Knowledge and Attitude in Preparing Disaster Drills? - Husna, Cut; Kamil, Hajjul; Yahya, Mustanir; Tahlil, Teuku; Darmawati, Darmawati (Nurse Media Journal of Nursing, 2020)
Background: Tabletop Exercise (TTE) is a specific learning method through a simulation designed to test the competency and the ability of a group to respond to disasters. Using the map of disaster events is considered effective to prepare disaster drills rather than other methods. TTE method has been carried out annually to train the students, however no studies reported the effect of this method.Purpose: The study aimed to evaluate the effect of TTE on enhancing nursing students’ knowledge and attitude in a disaster drill. Methods: This study was conducted with one-group pre and post-test of a quasi-experimental design. The total samplings were 80 nursing students of the fourth year who undertook the disaster nursing course. The intervention of the study was started using the scenario of an earthquake disaster simulation using TTE media divided into four groups. The instruments consisted of two questionnaires: Students’ Knowledge on Tabletop Exercise (SKTE), and Students' Attitude on Tabletop Exercise (SATE) which were tested for their validity and reliability. The data were analyzed using a dependent paired t-test. Results: The study showed that TTE had a positive effect in enhancing the knowledge (p=0.001) and the attitude of nursing students in disaster drills (p=0.001) (df=79). Conclusion: TTE intervention was an effective direct learning method to improve students’ competencies in disaster response. TTE might be considered as a learning method in improving students' competencies in preparing disaster drills.